Does the New Managerialism Stabilise Gender Asymmetries in Street-Level Interactions? The case of Germany after 'Hartz IV' - Karen Jaehrling (Social Work & Society, 2015)
The new 'basic allowance for job seekers' ('Hartz IV') introduced in Germany in 2005 was accompanied by a claim that 'activating' labour market policies would increase gender equality, not least by requiring mothers without a breadwinning partner to take up paid work and supporting them in doing so. At the same time, the reform gave rise to concerns that the enforcement of formal gender equality in terms of work obligations - hence a 'de-institutionalisation of gender differences' - might paradoxically increase gender inequality by forcing women to accept any job in the strongly gender-segregated labour market and by not adequately taking account of their caring responsibilities. However, the article, which is based on job centre case studies carried out in the first few years after the reform, shows that caseworkers' strategies for implementing the new law were, in part, quite similar to the routines established under the previous system. This was not due simply to the traditionalist attitudes of street-level bureaucrats anxious to 'protect' mothers against the 'adult worker model', but at least as much to the principles of the 'new managerialism' and its associated incentives that stabilise traditionalist attitudes and the resulting gender asymmetries.